Screening for and management of comorbidities after a nurse-led program: results of a 3-year longitudinal study in 769 established rheumatoid arthritis patients. Issue 2 (14th June 2019) - Gossec, Laure; Soubrier, Martin; Foissac, Frantz; Molto, Anna; Richette, Pascal; Beauvais, Catherine; Ruyssen-Witrand, Adeline; Perdriger, Aleth; Chary-Valckenaere, Isabelle; Mouterde, Gael; Dernis, Emanuelle; Euller-Ziegler, Liana; et al.
Abstract : Background/purpose: Cardiovascular (CV) risk, cancer, infections and osteoporosis should be screened for in rheumatoid arthritis (RA). The objective was to assess 3-year effects of a nurse visit for comorbidity counselling. Methods: This was an open long-term (3 years) extension of the Comorbidities and Education in Rheumatoid Arthritis 6-month randomised controlled trial in which patients with definite, stable RA were visiting a nurse for comorbidity counselling. Comorbidity status was assessed and nurses provided advice on screening and management, at baseline and 3 years later. A score was developed to quantify comorbidity screening and management: 0–100, where lower scores indicate better screening and management. The score was compared between baseline and 3-year assessment using a Wilcoxon test for paired data. Results: Of the 970 recruited patients, 776 (80%) were followed-up at 2–4 years and 769 (79%) had available data for comorbidities at both time points: mean (±SD) age 58 (±11) years and mean disease duration 14 (±10) years; 614 (80%) were women, the mean Disease Activity Score 28 was 3.0±1.3, and 538 (70%) were receiving a biologic. At baseline, the mean comorbidity screening score was 36.6 (±19.9) and it improved at 3 years to 24.3 (±17.8) (p<0.0001), thus with a relative improvement of 33% (improvement of 12 points). CV risk screening, vaccination status and bone densitometry performance improved the most. Conclusions: Comorbidity screening was suboptimal but improved notably over 3 years, after a nurse-led programme aiming at checking systematically for comorbidity screening and giving patient advice. This long-term efficacy pleads in favour of nurse-led interventions to better address comorbidities in RA. Trial registration number: NCT01315652